A case of parosteal osteosarcoma with a rare complication of myositis ossificans - Spinelli, Maria Silvia (BioMed Central, 2012)
We report the case of a parosteal osteosarcoma of the distal ulna, treated with wide resection without reconstruction. The patient developed lung metastasis and a mass in the interosseus membrane of the forearm proximally to the osteotomy. The lung mass was found to be a metastasis from parosteal osteosarcoma and the biopsy of the forearm mass revealed a myositis ossificans. The suspicion of a recurrence of parosteal osteosarcoma, already metastatic, led to a second wide resection with no reconstruction. A slice of the radial cortex was taken during this second procedure. From a histological point of view, good margins were achieved and diagnosis of myositis ossificans was confirmed. Two months later, a radius fracture occurred and a synthesis, with plate and screws, as added with poly(methyl methacrylate) (PMMA) to reconstruct the bone loss, was performed. Indication of the reconstructive technique and the complication after distal ulna resection in oncologic surgery are discussed in this paper.